THE RELATIONSHIP BETWEEN CAPITAL STRUCTURE COMPOSITION AND FINANCIAL PERFOMANCE OF LISTED FIRMS: A CRITICAL REVIEW OF LITERATURE - , Akali James Agembe (IJRDO - Journal of Business Management, 2019)
Capital structure is important in the business affairs of any going concern entity as its the overall source of finance used by a company in financing its operations and has been considered as one of the most important factors in firm financing policy due to its crucial role in corporate performance. The characterization of the relationship signs as positive or negative and the direction weather capital structure impacts on Financial performance of Firms both manufacturing and non-manufacturing are questions that authors have tried to answer for a long time. Financial performance is the blue print of the financial affairs of a concern and it reveals the organizations ability to translate its financial resources into mission related activities. The literature has laid down the inconsistencies as a result of different multi-sector samples and the multiplicity of financial performance of the Firms. Since these factors are apparently the originating causes of this inconsistency, there is need to address them particularly in the review of the literature that is available, this will allow the reflection of new trends in research and to highlight ways of enriching this research tradition. Decision about capital structure still remains one of the most challenging and most difficult issues facing companies, at the same time the most critical decision about the continued survival of companies. To study the relationship between capital structure composition and financial performance of Firms will help us know the potential problems in financial performance and capital structure.